The NECS Conference in Gdańsk, 2019. The Network for Cinema and Media Studies Goes Back to Eastern Europe Thirty Years after the Downfall of Communism - Tion, Lucian (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2019)
Lucian Tion`s review of the NECS Conference in Gdańsk, 2019